2011
DOI: 10.1021/ja2066225
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Polymers in Aqueous Medium: Rational Design Based on Directional Hydrophobic Interactions

Abstract: Self-assembly in aqueous medium is of primary importance and widely employs hydrophobic interactions. Yet, unlike directional hydrogen bonds, hydrophobic interactions lack directionality, making difficult rational self-assembly design. Directional hydrophobic motif would significantly enhance rational design in aqueous self-assembly, yet general approaches to such interactions are currently lacking. Here, we show that pairwise directional hydrophobic/π-stacking interactions can be designed using well-defined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 55 publications
1
55
0
2
Order By: Relevance
“…These assemblies revealed exciton confinement and localized emission, which are uncommon for extended π-stacked systems. 284 In another study, Yagai and co-workers reported on the selfassembly of bis-PBIs 3-38a−f (n = 5−10), which were connected through alkane linkers to control self-organized structures in both solution and solid state. 285 An odd/even effect of the linker units was observed due to the different molecular packing efficiencies, which influence the thermal as well as electronic properties and charge-carrier transportation characteristics of these bis-PBIs.…”
Section: Self-assembly Of Dye Arrays Composed Of Multiple Pbismentioning
confidence: 99%
“…These assemblies revealed exciton confinement and localized emission, which are uncommon for extended π-stacked systems. 284 In another study, Yagai and co-workers reported on the selfassembly of bis-PBIs 3-38a−f (n = 5−10), which were connected through alkane linkers to control self-organized structures in both solution and solid state. 285 An odd/even effect of the linker units was observed due to the different molecular packing efficiencies, which influence the thermal as well as electronic properties and charge-carrier transportation characteristics of these bis-PBIs.…”
Section: Self-assembly Of Dye Arrays Composed Of Multiple Pbismentioning
confidence: 99%
“…103 A rational design of supramolecular dynamers based on hydrophobic interactions has been realized in recent years. 104 Hexasubstituted benzene scaffolds decorated with amphiphilic perylene diimides (64 or 65) were observed to self-assembly into supramolecular polymers through pairwise hydrophobic/ π-stacking interactions in aqueous medium ( Figure 36). The association constants of 65 were determined to be as strong as 10 9 M −1 .…”
Section: Supramolecular Dynamersmentioning
confidence: 99%
“…The temperature dependent UV-vis absorption study performed in water: acetonitrile (ACN) (90:10) at a concentration of 3 × 10 -5 m revealed a cooperative pathway ( Figure S5d, Supporting Information). [45] Clear lattice planes were observed for the assembly in water with a d-spacing of 3.6 Å under high resolution TEM (inset Figure 2c). The transmission electron microscopy (TEM) images of PDPP-Amphi aggregates in MCH: chloroform (95:5) as well as in water: ACN (90:10) mixtures (5 × 10 -5 m) obtained upon drop casting over carbon coated copper grids are shown in Figure 2c.…”
mentioning
confidence: 97%